Writing with Precision: How Filipino ESL Learners Navigate Technical Terms and Context Clues - Herdiansyah, Yoseci Khairunnisa; Hardiyanto, Asep (J-SHMIC : Journal of English for Academic, 2026)
This study looked at how 25 Grade 10 ESL students in the Philippines use technical vocabulary and contextual clues in paragraph writing. Student writing was assessed using a four-point rubric covering terminology, contextual support, organization, and grammar, and analyzed through the framework of Miles and Huberman (1984). The results pointed to a clear tension between two things: students were surprisingly strong on technical vocabulary :  three of the five groups scored at the excellent level  but they struggled to actually build meaning around the terms they used. Groups that scored well did so by embedding technical terms within explanations that gave readers enough context to follow along. Groups that scored poorly used technical terms correctly but left them without support, so the words sat in the paragraphs without doing much communicative work. Grammar errors made this worse, particularly for students who were already struggling with contextual application. Scores ranged from 7 to 15 out of 16, with a mean of 10.8, which reflects how unevenly these skills were distributed across groups. The findings challenge the common assumption in ESL teaching that vocabulary acquisition is the first priority and that application will follow on its own. What the data actually show is that knowing technical terms and knowing how to use them strategically are two separate skills that need to be developed at the same time. These findings have direct relevance for ESL instruction in Southeast Asian contexts where English serves as the medium of instruction.